Unlocking Organizational Change Readiness: Exploring the Mediating Roles of Job Satisfaction and Job Engagement in the Impact of Organizational Culture - Ilzar Daud; Donny Usman; Rizky Fauzan; Nur Afifah (STIE AMKOP, 2023)
The current business conditions move very fast, to be able to survive in the midst of chaotic conditions, the key lies in one word, namely change. While every organizational change is unique because it involves individuals in it who are also unique. Changes whose birth process is not enough to only include key members but also require the involvement of all members of the organization. Not all changes made by the organization will be implemented effectively. One of the reasons change implementation often fails is the lack of readiness of employees to change. This study focuses on identifying the influence of organizational culture on employee readiness to change by mediated job satisfaction and work engagement. Employee readiness to change was measured using the Readiness To Change Questionnaire developed by Holt (2007). Organizational Culture was measured using the Denison Organizational Culture Scale (DOCS) by Denison (2004). Job satisfaction was measured using the Job Satisfaction Survey (JSS) by Spector (1997), while Work Engagement was measured using the Ultrecht Work Engagement Scale (UWES-9) by Schaufeli (2002). Data were collected from 1,139 employees working in Indonesian plantation companies. The results showed that organizational culture had a positive and significant influence on readiness to change (path coefficient = 0.426, t = 14,829, p